A metabolomics footprint approach to understanding the benefits of synbiotics in functional foods and dietary therapeutics for health, communicable and non-communicable diseases. (February 2020) - Cukkemane, Abhishek; Kumar, Prashant; Sathyamoorthy, Bharathwaj
Graphical abstract: Highlights: Metabolic Profiling of Probiotic fermented dairy product using NMR spectroscopy. Identification of biochemical pathways of major and minor metabolic constituents. Strategy to design synbiotic ferments using Lactic acid bacteria (LAB) co-cultures. Biochemical basis for anti-microbial activity and epithelial cell binding of LAB. Abstract: Gut microbiota have been shown to affect various cellular and host response elements such as immunological, neurological, energy, storage, etc. In recent years, this has led to rapid expansion in dietary products containing probiotics, prebiotics and combination thereof in synbiotics. While benefits of consuming functional foods derived from probiotics strains have been demonstrated for various metabolites, a detailed analysis of the biochemical footprints and their benefits remain under-studied. Herein, using a combination of NMR metabolomics, microbial techniques and cell-culture assays, we have characterized metabolite profiles of probiotic viz. Lactobacillus delbruekii ATCC 9649, Lactobacillus casei ATCC 335, Lactobacillus plantarum NRC 716 and Bacillus coagulans ATCC 12425 cultures in fermented milk. We identified predominance of sugars, small chain fatty acids, organic acids and branched chain amino acids from natural abundance 13 C NMR studies. Additionally, we identified myriad metabolites and their respective pathways using 1 H NMR spectroscopy. Based on our findings, synbiotic fermented dairy products were customized with co-cultures and complemented with pro- and pre- biotics. Furthermore, we demonstrate epithelial cell interaction and anti-microbial activity of L. plantarum based ferment against a range of bacterial pathogens highlighting possible biochemical mechanisms for anti-microbial activity, quorum sensing, gut colonization and other beneficial factors that may be crucial. Furthermore, we propose plausible explanation against non-communicable diseases such as tumor-inhibitory, anti-proliferative and pro-apoptotic effects which has direct implications for dietary therapeutics.